RUSSIAN AND FOREIGN VIEWS ON THE COLONIZATION PHENOMENON AND RESETTLEMENT PROCESSES IN THE RUSSIAN HISTORY - Ramzan Zubariev (Гуманитарные и юридические исследования)
The article scrutinizes the approaches and estimations of national and foreign scientists of different generations, investigating aims, forms and the character of colonization and resettlement movement in the history of Russia. Russian and foreign authors point to the distinctions to appraise the essence of the phenomena. Some of them consider the latter as the expansion of the Russian Empire, its desire to dominate. At the same time, the others confirm that colonization and resettlement movement are the form of state building and the way to decide social, economic and cultural tasks aimed at crisis overcoming. For instance, the peasants' migration to eastern borderlands became the instrument to tackle the acuteness of a land crisis in Central Russia provinc es, but as well as to create in their face the basis of the government in new residences. The initiative and activity of the state in the organization of new lands colonization actualized at the stage of its military expansion to the neighboring territories, though such type of colonization was not the dominant one in Russian history. Having consolidated new state borders by Cossacks' settling, Russian authorities, directly or indirectly, promoted industrial and cultural development of new territories, included them in the civil existence, political and judicial system of the Empire.